Student perceptions of online and in-person microbiology laboratory experiences in undergraduate medical education - Brockman, Ross M. (Med Educ Online, 2020)
Background: Universities are facing increased budget constraints, often resulting in reduced funds to support microbiology laboratories. Online mock laboratory activities are often instituted as a cost-effective alternative to traditional wet labs for medical students. Objective: The purpose of this study was to examine students’ perceptions of online and in-person microbiology lab learning experiences. Design: We investigated undergraduate medical student perception of the in-person and online microbiology lab experience; 164 first-year medical students participated in newly designed online labs, while 83 second-year medical students continued to use in-person labs. An online survey was administered to collect student opinions of the lab experience. Results: In terms of student self-reported learning styles, those students who attended the lab in person were more likely to report a tactile learning style (33% vs 16%) while those students who learned the material online reported a visual learning style preference (77% vs 61%; n = 264). Students felt that the online microbiology lab was more convenient for their schedules when compared to the in-person lab. A greater proportion of online students (12%) felt that they encountered brand-new material on the final quiz than in-person students (1%; n = 245). Even so, 43% of the online educated students and 37% of the in-person educated students perceived their assigned lab experiences to be the optimal lab design, and over 89% of both groups reported a desire for at least some in-person instruction in a wet-laboratory environment. Conclusions: Our findings suggest that, while students are strongly supportive of digital online lab activities, the overwhelming majority of students still report a desire for a blend of online and in-person, hands-on laboratory activities. These findings will further research directed towards student perception of the lab experience and aid in the adaptation of microbiology curriculums to accommodate both student and university needs.